0664 A Low Arousal Threshold Causes Bad Shift of Positive Airway Pressure Compliance Over Time in Obstructive Sleep Apnea Patients. (27th May 2020) - Wu, H; Wei, Y; Fang, F
Abstract: Introduction: To determine the predictive factors of initial and long-term adherence to positive airway pressure (PAP) therapy and which factors leading a shift of good initial compliance to noncompliance. Methods: In this follow-up study, A cohort of 166 adult patients who underwent polysomnography (PSG) between January 2017 and April 2019, newly diagnosed with obstructive sleep apnea (OSA) and were amenable to PAP therapy were selected. Information on basic demographics, comorbidities and sleep-related symptoms was collected. PAP adherence data were collected at the end of the first week and the third month. After 3 months of follow-up, 142 participants were included for final data analysis. Results: Pressure levels were stable during 3 months of PAP treatment. Overall average daily usage time and percentage of PAP used days ≥4 hrs were lower for 3 months than that in the first week. After adjustment for age and gender, multinomial logistic regression analysis showed that less number of sleep-related symptoms (OR, 0.69; 95% CI, 0.52-0.91) and low arousal threshold (ArTH) (OR, 4.44; 95% CI, 1.52-12.98) were associated with a higher odds of consistent noncompliance of PAP; Low ArTH (OR, 2.87; 95% CI, 1.09-7.57) and less BIM (OR, 0.88; 95% CI, 0.78-0.99) increased the risk of compliance-to-noncompliance shift. Conclusion: Different from the predictors of consistent PAP noncompliance of OSA patients, only less BMI and low ArTH would cause a good PAP compliance shift to noncompliance over time. Support: Science and technology Beijing 100 leading talents (Z171100001117168)